An experimental study on the dynamic flexural tensile behavior of glass. (1st May 2022) - Jiang, Bin; Atif, Muhammad; Ding, Yi; Guo, Yazhou; Li, Yulong
Graphical abstract: Abstract: Understanding of the dynamic tensile behavior of glasses is of great importance in designing impact-resistant transparent structures. The current study revealed the effects of loading rate, specimen size and stress wave on the dynamic tensile behavior of brittle glass. The quasi-static, unidirectional (UD) and uniaxial bidirectional (BD) dynamic tests were systematically performed. The electromagnetic split Hopkinson pressure bar (ESHPB), which is able to launch simultaneously two stress pulses from two opposite directions, was introduced for dynamic flexural test. A high-speed photography system was used to capture the failure process of the specimen. The test results demonstrated that the loading rate and specimen size affected the measured flexural strength significantly. The captured images revealed that the dynamic tensile stress within the specimen reached its maximum at the same time as the crack starts. The flexural strength measured from dynamic UD and BD tests were essentially equivalent, which is different from the dynamic compressive strength of brittle materials. Fractographic analysis was also carried out using a scanning electron microscope (SEM) and the flexural tensile failure mechanism was discussed.